VISUAL COMPROMISE IN PREGNANCY: AN UNPRECEDENTED CASE OF NON-FUNCTIONING PITUITARY MACROADENOMA - Bernard, Dorothy Maria Anthony; Ratnasingam, Jeyakantha (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Non-functioning pituitary macroadenoma (NFPA) diagnosed during pregnancy is extremely rare. A 24-yearold Malaysian female presented at 20 weeks age of gestation with bilateral blurring of vision. She had bitemporal hemianopia with no Cushing’s or acromegalic features. She had intact anterior pituitary hormones and normal prolactin. Brain imaging revealed a pituitary macroadenoma (3 x 2 cm) with optic chiasm compression without evidence of apoplexy or cavernous sinus involvement. She was commenced on cabergoline to reduce the tumour size. Despite this, she developed progressively worsening vision. She underwent an emergency caesarean section and delivered a baby boy prematurely. Subsequently, she had transsphenoidal surgery 2 weeks post-delivery. Histopathology confirmed pituitary adenoma. Postoperatively, there was complete resolution of bitemporal hemianopia, with no residual tumour on imaging and she remained eupituitary. We present a unique case of visual compromise from an enlarging NFPA during pregnancy with complete resolution of symptoms post-resection.